2015
DOI: 10.18805/asd.v35i4.6855
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path analysis of morpho-physiological and yield traits in <italic>boro</italic> rice (<italic>Oryza sativa</italic> L.)

Abstract: Thirty rice genotypes of local and exotic origin were analyzed to ascertain the genotypic and phenotypic correlation among 21 morpho-physiological and yield traits and their direct/ indirect contribution to grain yield under boro season. The result revealed that grain yield per plant had significant positive correlation with biological yield (0.927**, 0.766**), harvest index (0.748**, 0.658**), days to first flowering (0.459*, 0.377*), panicle length (0.501**, 0.445*), grains per panicle (0.576**, 0.484**) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The length/ breadth ratio of the grain showed a significantly positive correlation with an average length of the grain (0.30), plant height at vegetative stage (0.28), and negative correlation with the weight of 1000 grain (-.48) and total yield/plot (-0.23). Similar outcomes were also stated by different researchers SUNYA ET AL 911 (Akhter et al, 2004;Chhangte et al, 2019 andDas et al, 2015).…”
Section: Correlation Between Yield and Plant Characterssupporting
confidence: 84%
See 1 more Smart Citation
“…The length/ breadth ratio of the grain showed a significantly positive correlation with an average length of the grain (0.30), plant height at vegetative stage (0.28), and negative correlation with the weight of 1000 grain (-.48) and total yield/plot (-0.23). Similar outcomes were also stated by different researchers SUNYA ET AL 911 (Akhter et al, 2004;Chhangte et al, 2019 andDas et al, 2015).…”
Section: Correlation Between Yield and Plant Characterssupporting
confidence: 84%
“…Similar results have been reported by Zhang et al (2017). Das et al (2015) examined 30 rice germplasm of exotic and local origin to ascertain the phenotypic as well as genotypic correlation among twenty one morpho-physiological and yield parameters and their indirect/direct contribution to the grain yield under boro season. The result obtained clearly indicated that the grain yield/plant had a significant correlation (positive) with the biological yield, harvest index, days to flowering, panicle length, grain/panicle, and the weight of the 1000 grain at both phenotypic as well as genotypic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Rice breeders also often face the problem of negative correlations among different yield traits (Sandhu et al, 2013 ; Ranawake and Amarasinghe, 2014 ), such as grain number per panicle (GNP), panicle number per plant (PN), kilo-grain weight (KGW), and rate of seed setting (Sakamoto and Matsuoka, 2008 ; Zhao et al, 2016 ). Many published works suggest that there is a disadvantageous positive correlation between heading date (HD) and GNP, but negative correlations among yield traits (Das and Sarma, 2015 ; Kharb et al, 2016 ). Most high-yield varieties have long growth duration in regions with adequate light and energy resources because longer growth duration provides more metabolic activity and nutrition for grain filling (Okada et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of trait correlations are the most important issues to be considered in breeding, such as the negative correlation between grain number per panicle and panicle number, and between grain number per panicle and kilo-grain weight 25 , positive correlation between heading date and grain yield per plant, and between heading date and grain number per panicle 25 , 65 and positive correlation between root weight and shoot weight in this study. Pleiotropy and LD are two considerable factors responsible for trait correlations, and it is hard to distinguish them in a short physical interval.…”
Section: Discussionmentioning
confidence: 82%